Result based management and service delivery: the case study of Buhera Rural District Council. - Chakanetsa, Sipiwe (Midlands State University, 2017)
The research analyses the link between Results Based Management and service delivery, the case of Buhera Rural District Council was used. Results Based Management is a new concept introduced in local authorities as a panacea to improve service delivery since most local authorities have been performing poorly in service provision. The Buhera Rural District Council is one of the few local authorities which have adopted Results Based Management in Zimbabwe. In the introductory chapter the researcher highlighted the background of the study citing the history of the council and the concept of Results Based Management. The statement of the problem inquired whether RBM has improved service delivery in Buhera or not. The research aims to identity- the reasons for adopting Results Based Management in local authorities, to examine how Results Based Management works, to determine the link between Results Based Management and service delivery and to determine the impact of Results Based Management on service delivery. Hence RBM is directly linked to service delivery. The researcher used descriptive and case study research designs in carrying out the research. A target population of 35 people and a sample of 25 respondents comprising of management, council employees and councillors was used. The researcher used judgmental sampling to select councillors and management as well as simple random sampling to select employees. Questionnaires and interviews were used as research instruments. The data collected was analyzed and presented in form of graphs, pie charts, frequency tables and tables. The findings of the study showed that BRDC has extremely improved in service delivery because of the introduction of RBM. It has improved in infrastructural development, social services, environmental management and in performance management and budgetary control. . However, the employees have capacity problems because of low educational levels, the community has problems in identify projects and programs and the local authority is facing financial challenges to carry out identified projects and programs. The research recommends the council to sensitize stakeholders about RBM to train RBM trainers who would train employees and to have purposive funding for identified projects and programme.